Proceedings of the 4th International ICST Conference on Pervasive Computing Technologies for Healthcare 2010
DOI: 10.4108/icst.pervasivehealth2010.8914
|View full text |Cite
|
Sign up to set email alerts
|

The self-management of chronic illnesses: Theories and technologies

Abstract: A patient who is self-managing a chronic condition is actively involved in the prevention, understanding and regulation of his symptoms by means of his behavior and choices. We present the most acknowledged self-management theories and strategies, with an accent on those that can be relevant for supporting leT solutions for Healthcare. Finally we review five projects about sensing technologies, mobile devices and ambient information displays for self-care and behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[9], promoting health education in children [10], and for changing existing social beliefs and health practices of rural women in a positive manner [11].…”
Section: Related Research In Persuasive Healthcarementioning
confidence: 99%
“…[9], promoting health education in children [10], and for changing existing social beliefs and health practices of rural women in a positive manner [11].…”
Section: Related Research In Persuasive Healthcarementioning
confidence: 99%
“…Therefore, the world is facing a critical issue: to lower or defer incidence rates of chronic disease and to solve issues related to long-term care. Numerous studies have indicated that behaviour change is the most effective precaution and self-care method for chronic patients [2][3][4]. Although patient behaviour changes seem to be very personal, family caregivers' acknowledgement of patients' positive behaviour changes could effectively enhance the quality of patient self-care.…”
Section: Introductionmentioning
confidence: 99%
“…The Self-Management of a chronic condition implies a shifting of responsibility from the Healthcare professional to the patient, who is actively involved in facing the different aspects of his illness and in engaging in behaviors that improve his health conditions (Torsi et al, 2010). This paper is focused on a process of Participatory Design (Blythe et al, 2002) between Health and Social Care researchers, chronically ill patients and designers of Human-Computer Interaction (HCI) and it is in particularly based on stroke, heart failure, diabetes and chronic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication (Torsi et al, 2010), some theories that explain different strategies by which a chronically ill patient can self-manage his condition are gathered and fully described. Such as, the Self-Efficacy, the Transtheoretical Model, Acceptance and Commitment Therapy, and Activity Pacing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation